Key performance indicators and industry 4.0: A socially responsible perspective - Simona Šarotar Žižek; Zlatko Nedelko; Matjaž Mulej; Živa Veingerl Čič (Naše gospodarstvo / Our Economy, 2020)
The main aim of this contribution is to outline the role and importance of key performance indicators in the frame of Industry 4.0 implementation. These key performance indicators are presented as a cornerstone for industry 4.0 implementation in organizational practice, since they represent key input for needed data in digitalized organization. In that framework, the contribution first exposes some of the essential characteristics of "Industry 4.0", followed by the methodology of key performance indicators (KPI). Next, the contribution outlined a proposed methodology for implementing KPIs in frame of Industry 4.0 adoption in organizations. Another section of the paper is dedicatd to the linkage between corporate social responsilbty and KPIs in frame of Industry 4.0. The paper also outlines implications, limitations and further research directions are outlined.
Keywords: M11; M12; 330; Industry 4.0; key performance indicators (KPI); social responsibility